Keragaman Pangan dengan Status Kadarzi Keluarga di Wilayah Kerja Posyandu Sidotopo, Surabaya - Samara Ika Soegeng Prakoso; Bibit Mulyana (Amerta Nutrition, 2018)
Background: Indonesia still facing some nutritional problems that hinder its economics development. The government itself has an effort to tackle nutritional problems by establishing  a program known as Keluarga Sadar Gizi (Kadarzi). The family expected to understand and overcome the nutritional problems affecting its members. One of Kadarzi’s five indicator is dietary diversity. Dietary divesity can reflected dietary quality. Therefore, dietary diversity assessment is influential to improve dietary quality. Objectives: The purpose of this study was to analyze the differences in dietary diversity scores among Kadarzi household. Method: The design of the study was cross sectional. Number of sample were 34 mothers who registered in Posyandu settled in Kelurahan Sidotopo, Kecamatan Semampir, Kota Surabaya. Samples were selected using simple random sampling technique. Kadarzi data were collected from KMS book. Dietary diversity was assessed using Individual Dietary Diversity Score (IDDS). The data were analyzed using independent T-test. Result: The result showed that most families were not meeting Kadarzi’s indicator (73%). There were 32.4% family categorized as low dietary diversity, 47.1% family categorized as medium dietary diversity, and 20.6% family categorized as high dietary diversity. There were a difference of dietary diversity score beetwen Kadarzi’s household nor Kadarzi’s household (p<0.001). In Kadarzi’s household the consumption of dark green leafy vegetables, other vitamin A rich fruits and vegetables, anf other fruits and vegetables are higher than non Kadarzi’s household. Conclusions: There was a significant difference in dietary diversity score beetwen Kadarzi’s household and nor Kadarzi’s household. The importance of eating diverse and some references of affordable food choice to meet dietary diversity were needed to share.ABSTRAKLatar belakang: Indonesia masih menghadapi beberapa masalah gizi yang menghambat perkembangan ekonomi. Namun pemerintah memiliki suatu upaya untuk mengatasi permasalahan gizi tersebut dengan membentuk program Keluarga Sadar Gizi (Kadarzi). Pada program ini keluarga diharapkan mampu mengerti dan mengatasi permasalahan gizi anggotanya. Salah dari lima perilaku Kadarzi adalah makan beragam. Makan beragam merupakan salah satu perilaku yang dapat menggambarkan kualitas diet individu. Oleh karena itu penilaian keragaman pangan perlu diketahui untuk mengetahui dan meningkatkan kualitas diet individu. Tujuan: Tujuan penelitian ini adalah untuk menganalisis perbedaan skor keragaman pangan pada keluarga sadar gizi. Metode: Penelitian observasional ini disusun dengan rancang bangun cross sectional. Sejumlah 34 sampel yang merupakan ibu balita yang terdaftar di Posyandu di wilayah Kelurahan Sidotopo, Kecamatan Semampir, Kota Surabaya dipilih menggunakan teknik simple random sampling. Data Kadarzi didapatkan dari observasi kartu menuju sehat (KMS). Keragaman pangan dinilai menggunakan instrumen Individual Dietary Diversity Score (IDDS). Data dianalisis menggunakan independent T-test. Hasil: Sebagian besar keluarga masih belum menerapkan perilaku Kadarzi (73%). Sebanyak 32,4% keluarga termasuk dalam kategori skor keragaman pangan rendah, 47,1% dalam kategori sedang, dan 20,6% dalam kategori tinggi. Terdapat perbedaan skor keragaman pangan antara keluarga yang menerapkan perilaku Kadarzi dan tidak menerapkan perilaku Kadarzi (p<0,001). Pada keluarga yang menerapkan perilaku Kadarzi konsumsi sayuran hijau, sayur dan buah vitamin A, sayur dan buah yang lain lebih tinggi daripada keluarga yang tidak menerapkan Kadarzi. Kesimpulan: Terdapat perbedaan skor keragaman pangan antara keluarga yang menerapkan perilaku Kadarzi dan tidak menerapkan perilaku Kadarzi. Diperlukan pemaparan informasi lebih lanjut mengenai pentingnya makan beragam dan pemilihan makanan yang terjangkau untuk dapat memenuhi konsumsi makan beragam.